2012
DOI: 10.1613/jair.3540
|View full text |Cite
|
Sign up to set email alerts
|

Improving Statistical Machine Translation for a Resource-Poor Language Using Related Resource-Rich Languages

Abstract: We propose a novel language-independent approach for improving machine translation for resource-poor languages by exploiting their similarity to resource-rich ones. More precisely, we improve the translation from a resource-poor source language X 1 into a resourcerich language Y given a bi-text containing a limited number of parallel sentences for X 1 -Y and a larger bi-text for X 2 -Y for some resource-rich language X 2 that is closely related to X 1 . This is achieved by taking advantage of the opportunities… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…Non-parallel co-learning approaches can help when learning representations, allow for better semantic concept understanding and even perform unseen object recognition. [148] Transfer learning is also possible on non-parallel data and allows to learn better representations through transferring information from a representation built using a data rich or clean modality to a data scarce or noisy modality. This type of trasnfer learning is often achieved by using coordinated multimodal representations (see Section 3.2).…”
Section: Non-parallel Datamentioning
confidence: 99%
“…Non-parallel co-learning approaches can help when learning representations, allow for better semantic concept understanding and even perform unseen object recognition. [148] Transfer learning is also possible on non-parallel data and allows to learn better representations through transferring information from a representation built using a data rich or clean modality to a data scarce or noisy modality. This type of trasnfer learning is often achieved by using coordinated multimodal representations (see Section 3.2).…”
Section: Non-parallel Datamentioning
confidence: 99%
“…This can be implemented by making the machine learn from various iterations of combining and adjusting the scores accordingly. (Nakov and Ng, 2012) have indeed shown that results show significant deviations associated with different weights assigned to the tables.…”
Section: Future Workmentioning
confidence: 89%
“…It should be noted that this issue does not arise only in the case of Arabic dialects; it concerns also several other under-resourced languages and many research activities focus on machine translation in the context of under-resourced or non-resourced languages. The main idea of these contributions is exploiting the proximity between an under-resourced language and the closest related resourced language (Cantonese⇒Mandarin (Zhang, 1998), Czech⇒Slovak (Hajič et al, 2000), Turkish⇒Crimean Tatar (Altintas and Cicekli, 2002), Irish⇒Scottish Gaelic (Scannell, 2006), Indonesian⇒English using Malay (Nakov and Ng, 2012) and Standard Austrian German⇒Viennese dialect (Haddow et al, 2013)).…”
Section: Nlp Challenges For Arabic Dialectsmentioning
confidence: 99%